2016
DOI: 10.1186/s13071-016-1602-6
|View full text |Cite
|
Sign up to set email alerts
|

T follicular helper cells in patients with acute schistosomiasis

Abstract: BackgroundThe role of T follicular helper (Tfh) cells in schistosome infection is not fully defined. In a previous study, a higher frequency of circulating PD-1+CXCR5+CD4+ Tfh cells was observed in patients with chronic schistosomiasis relative to healthy controls (HCs) and it correlated positively with the level of soluble egg antigen (SEA) specific antibodies in serum. However, the function of Tfh cells in patients with acute schistosomiasis remains elusive; this was investigated in the present study.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 28 publications
1
16
1
Order By: Relevance
“…Wang et al found that, in murine schistosomiasis, Tfh cells accumulate in the splenic germinal center and that the Tfh phenotypic molecule, Bcl-6, and the Tfh-type cytokine, IL-21, correlate with progression of liver fibrosis (92). In addition, clinical studies have shown that Tfh cells are involved in immune responses for both acute and chronic human schistosomiasis (93,94). The frequency of circulating PD-1 + CXCR5 + CD4 + Tfh cells in the peripheral blood is increased in both acute and chronic schistosomiasis patients relative to healthy controls.…”
Section: Tfh Promotes Liver Pathology Of Schistosomiasismentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al found that, in murine schistosomiasis, Tfh cells accumulate in the splenic germinal center and that the Tfh phenotypic molecule, Bcl-6, and the Tfh-type cytokine, IL-21, correlate with progression of liver fibrosis (92). In addition, clinical studies have shown that Tfh cells are involved in immune responses for both acute and chronic human schistosomiasis (93,94). The frequency of circulating PD-1 + CXCR5 + CD4 + Tfh cells in the peripheral blood is increased in both acute and chronic schistosomiasis patients relative to healthy controls.…”
Section: Tfh Promotes Liver Pathology Of Schistosomiasismentioning
confidence: 99%
“…The frequency of circulating PD-1 + CXCR5 + CD4 + Tfh cells in the peripheral blood is increased in both acute and chronic schistosomiasis patients relative to healthy controls. However, the difference between acute and chronic schistosomiasis is that there is no correlation between percentages of PD-1 + CXCR5 + CD4 + Tfh cells, memory B cells, or the level of immunoglobulin G (IgG) specific to S. japonicum antigen in acute schistosomiasis patients; however, frequency of PD-1 + CXCR5 + CD4 + Tfh cells is positively correlated to the levels of IL-21 in sera and the levels of SEA-specific antibody in chronic schistosomiasis patients (93,94). These findings demonstrate that Tfh cells might exhibit distinct mechanisms to regulate the immune response between acute and chronic schistosomiasis.…”
Section: Tfh Promotes Liver Pathology Of Schistosomiasismentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms of immunomodulation include IL-10, T regulatory cells, B cells, antibodies, and T cell anergy [12][13][14][15]. Besides, several studies have suggested that Th17 cells are involved in the pathogenesis of both S. mansoni and S. japonica [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Tfh cells can promote antigen-specific B cell activation, germinal center formation and humoral responses [12,13]. In addition, Tfh cells are involved in the pathogenic process of some autoimmune diseases [14-16] and participate in defensing against parasite infection [17,18]. Indeed, increased frequency of Tfh cells is detected in rodent with S. japonicum infection and Tfh cells activated by ICOS + macrophages infiltrate into the liver and enhance the liver injury in mice infected with S. japonicum [19].…”
Section: Introductionmentioning
confidence: 99%